PERANAN INSPEKTORAT DAERAH DALAM RANGKA MENINGKATKAN GOOD GOVERNMENT PENYELENGGARAAN PEMERINTAHAN DESA (STUDI KASUS PADA DESA TERTINGGAL DI KABUPATEN BLITAR) - Furri Trisnawati (Universitas Islam Kadiri, 2020)
Since the birt of the village law gives a great responsibility to the village government with special authority to regulate the village. Giving a big responsibility is not accompanied by a good preparation of human resources. As a result, the birth of good governance in the village government environment is still far from expectations. On the other hand grating village autonomy gave birth to new bags of corruption in the country. This study aims to determine the principles of supervision that are applied to support the good governance of village governments, especially in underdeveloped villages in Blitar district. This research uses a qualitative method with case studies conducted through interviews and documentation. The principle of supervision has been implemented by the inspectorate but weaknesses are still found with the main factors The principle of supervision has been implemented by the inspectorate but weaknesses are still found with the main. This research is expected to provide benefits to the inspectorate to improve performance and to the village government to implement the results of supervision to make improvements in accordance with applicable regulations.